Expected residual service life of reinforced concrete structures from current strength considerations. Issue 7 (May 2019) - Dhawan, Sushil Kumar; Bindal, Abhinav; Bhalla, Suresh; Bhattacharjee, Bishwajit
Concrete is primarily used in the form of reinforced concrete for construction of buildings, bridges and other important structures. Due to normal usage and environmental effects, the structure would gradually deteriorate. The actual residual life needs to be worked at a given time vis-à-vis the design life of the structure, commensurate with the fulfilment of essential requirements of structural integrity and safety and from strength as well as serviceability considerations. Requirements for residual life assessment would depend upon the current parameters, such as the residual cross-sectional area of concrete as well as steel, Young's modulus of elasticity and the in situ material strength of the constituent materials, namely, concrete and steel. This article aims to develop a rigorous methodology for expected remaining service life of a reinforced concrete structure from wind/seismic considerations, based on the present condition of the structure encompassing the residual material strength and the residual reinforcement/sectional areas. The methodology development section is followed by an illustrative example and a parametric study involving a 10-storeyed reinforced concrete building frame under wind and earthquake loads. Influences of various parameters such as concrete strength and residual rebar area on the expected remaining service life are studied in detail. The proposed methodology provides a simple but rational estimation of the residual service life for reinforced concrete structures.